1956
DOI: 10.1039/jr9560002823
|View full text |Cite
|
Sign up to set email alerts
|

552. The oxidation of monohydric phenols by alkaline ferricyanide

Abstract: The initial stage of oxidation of phenols by alkaline ferricyanide appears to be a reversible reaction between the phenol anion and the ferricyanide ion, giving ferrocyanide and a mesomeric aryloxy-radical. Irreversible reactions then follow, giving mixtures of dimeric and polymeric products. Though the rate of oxidation is dependent upon the alkalinity of the solution and on the [Ferricyanide] /[Ferrocyanide] ratio, Fieser's theory 1 concerning a " critical oxidation potential " for attack on a phenol gives f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Earlier reports on the oxidative treatment of 1 with metals in high oxidation states gave reasonable yields of the desired biphenol only in catalytic approaches, [5][6][7] whereas methods employing stoichiometric amounts of the oxidizing agent or electrochemical oxidation often lack selectivity or resulted in poor yields. [8,9] In the course of our investigations we detected besides biphenol 2 and Pummerer's ketone 3 four other distinct products, which appeared reliably. Depending on the reaction conditions these particular compounds arose in notable quantities.…”
Section: Resultsmentioning
confidence: 84%
“…Earlier reports on the oxidative treatment of 1 with metals in high oxidation states gave reasonable yields of the desired biphenol only in catalytic approaches, [5][6][7] whereas methods employing stoichiometric amounts of the oxidizing agent or electrochemical oxidation often lack selectivity or resulted in poor yields. [8,9] In the course of our investigations we detected besides biphenol 2 and Pummerer's ketone 3 four other distinct products, which appeared reliably. Depending on the reaction conditions these particular compounds arose in notable quantities.…”
Section: Resultsmentioning
confidence: 84%
“…When larger amounts molecular weight yellow resin). 29 These reactions of TMEDA were added the molecular weight presumably proceed through a phenoxy radical 12 obtained was further increased. Instead of using intermediate.…”
Section: 23mentioning
confidence: 99%
“…Another control reaction (Table 1, entry 2) revealed that the oxidation of DMP with an equal amount of base and potassium ferricyanide in water predominantly gave DPQ and a small amount of the phenyleneoxide oligomer (M n = 4.0 10 2 , M w /M n = 1.5) as previously reported. [6,8] We found that the oxidation of DMP resulted in polymerization at an optimal temperature of 50 8C in the presence of excess base (relative to the monomer) (Table 1, entry 5); [12] significantly, DPQ formation was suppressed to less than 0.4 %.…”
mentioning
confidence: 99%
“…[6,7] The oxidation of DMP in water is well-known to give predominantly DPQ (3), which is formed by the CÀC coupling of two monomeric phenols (Scheme 1). [6,8] There is another unsolved problem associated with polymerization in water: The dimer of DMP is insoluble, even in an alkaline aqueous solution, and the molecular weight of the formed PPO remains very low. We have now succeeded in oxidatively polymerizing DMP to form high-molecular-weight PPO in water.…”
mentioning
confidence: 99%